Postcolonial migrants and identity politics : Europe, Russia, Japan and the United States in comparison - Bosma, Ulbe, 1962-; Lucassen, Jan; Oostindie, Gert (International studies in social history ;, 2012)
These transfers of sovereignty resulted in extensive, unforeseen movements of citizens and subjects to their former countries. The phenomenon of postcolonial migration affected not only European nations, but also the United States, Japan and post-Soviet Russia. The political and societal reactions to the unexpected and often unwelcome migrants was significant to postcolonial migrants' identity politics and how these influenced metropolitan debates about citizenship, national identity and colonial history. The contributors explore the historical background and contemporary significance of these.